2020
DOI: 10.2196/19468
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Supportive Interventions for Family Caregivers of People With Dementia: Systematic Review and Meta-Analysis

Abstract: Background Caring for people with dementia is perceived as one of the most stressful and difficult forms of caring. Family caregivers always experience high levels of psychological burden and physical strain, so effective and practical support is essential. Internet-based supportive interventions can provide convenient and efficient support and education to potentially reduce the physical and psychological burden associated with providing care. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 51 publications
2
85
1
5
Order By: Relevance
“…The main benefits regard emotional well-being (depression, anxiety, stress, and burden), learned skills (decision making, knowledge, self-efficacy, and strategies), and social aspects (perceived support and positive aspects related to caregiving, such as bonding with your relative; (McKechnie et al, 2014 ; Dam et al, 2016 ; Egan et al, 2018 ; Ruggiano et al, 2018 ). Moreover, despite the few quantitative analyses and the limits concerning the adopted methodologies, results highlighted the benefits online interventions have for what concerns caregivers' quality of life (Boots et al, 2014 ; Waller et al, 2017 ; Leng et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The main benefits regard emotional well-being (depression, anxiety, stress, and burden), learned skills (decision making, knowledge, self-efficacy, and strategies), and social aspects (perceived support and positive aspects related to caregiving, such as bonding with your relative; (McKechnie et al, 2014 ; Dam et al, 2016 ; Egan et al, 2018 ; Ruggiano et al, 2018 ). Moreover, despite the few quantitative analyses and the limits concerning the adopted methodologies, results highlighted the benefits online interventions have for what concerns caregivers' quality of life (Boots et al, 2014 ; Waller et al, 2017 ; Leng et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review found that internet-based supportive interventions are effective in improving self-efficacy, depressive symptoms, and stress, but the effects on burden, caregiver reaction to behavioural symptoms, and coping competence were not significant. ( 4 )…”
Section: Discussionmentioning
confidence: 99%
“…( 2 ) Recent systematic reviews and meta-analyses have found some evidence of positive effects of online interventions for caregivers of PwD, particularly for outcomes of caregiver stress, ( 4 ) self-efficacy, ( 4 ) burden, ( 5 9 ) and depression/anxiety. ( 4 7 , 9 , 10 ) Multi-component interventions show the strongest effects. ( 6 , 8 10 )…”
Section: Introductionmentioning
confidence: 99%
“…This care model has successfully operated for nearly a decade in an Indianapolis health care system 490 . Other efforts have attempted to broaden the reach and accessibility of interventions for dementia caregivers through the use of technologies (for instance, video‐phone delivery and online training), 491–497 while others have integrated evidence‐based dementia care interventions into community‐based programs 489 …”
Section: Caregivingmentioning
confidence: 99%